Disruption of endosomal trafficking with EGA alters TLR9 cytokine response in human plasmacytoid dendritic cells - Wiest, Matthew J.; Gu, Chao; Ham, Hyoungjun; Gorvel, Laurent; Keddis, Mira T.; Griffing, Leroy W.; Joo, HyeMee; Gorvel, Jean-Pierre; Billadeau, Daniel D.; Oh, SangKon (Frontiers in Immunology, 2023)
Plasmacytoid dendritic cells (pDCs) exhibit bifurcated cytokine responses to TLR9 agonists, an IRF7-mediated type 1 IFN response or a pro-inflammatory cytokine response via the activation of NF-B. This bifurcated response has been hypothesized to result from either distinct signaling endosomes or endo-lysosomal trafficking delay of TLR9 agonists allowing for autocrine signaling to affect outcomes. Utilizing the late endosome trafficking inhibitor, EGA, we assessed the bifurcated cytokine responses of pDCs to TLR9 stimulation. EGA treatment of pDCs diminished both IFN and pro-inflammatory cytokine expression induced by CpG DNAs (D- and K-type), CpG-DNAs complexed with DOTAP, and genomic DNAs complexed with LL37. Mechanistically, EGA suppressed phosphorylation of IKK/, STAT1, Akt, and p38, and blocked TLR9 processing which corresponded with decreased colocalization of CpG oligodeoxynucleotides with LAMP+ endo-lysosomes. EGA also diminished type 1 IFN expression by pDCs from systemic lupus erythematosus patients. Therefore, our findings help understand mechanisms for the bifurcated cytokine responses by pDCs and support further examination of potential benefit of EGA in treating type 1 IFN-associated inflammatory diseases in the future.